B-cell-specific MhcII regulates microbiota composition in a primarily IgA-independent manner - Roland, Mary Melissa; Peacock, Tori E.; Hall, Nia; Mohammed, Ahmed Dawood; Ball, Ryan; Jolly, Amy; Alexeev, Sergei; Dopkins, Nicolas; Nagarkatti, Mitzi; Nagarkatti, Prakash; Kubinak, Jason L. (Frontiers in Immunology, 2023)
Background The expression of major histocompatibility complex class II (MhcII) molecules on B cells is required for the development of germinal centers (GCs) in lymphoid follicles; the primary sites for the generation of T-cell-dependent (TD) antibody responses. Peyer’s patches (PPs) are secondary lymphoid tissues (SLOs) in the small intestine (SI) that give rise to high-affinity, TD antibodies (mainly immunoglobulin A (IgA)) generated against the microbiota. While several studies have demonstrated that MhcII antigen presentation by other immune cells coordinate TD IgA responses and regulate microbiota composition, whether or not B-cell-specific MhcII influences gut microbial ecology is unknown. Methods Here, we developed a novel Rag1-/- adoptive co-transfer model to answer this question. In this model, Rag1-/- mice were reconstituted with naïve CD4+ T cells and either MhcII-sufficient or MhcII-deficient naïve B cells. Subsequent to this, resulting shifts in microbiota composition was characterized via 16S rRNA gene sequencing of SI-resident and fecal bacterial communities. Results Results from our experiments indicate that SLO development and reconstitution of an anti-commensal TD IgA response can be induced in Rag1-/- mice receiving T cells and MhcII-sufficient B cells, but not in mice receiving T cells and MhcII-deficient B cells. Results from our 16S experiments confirmed that adaptive immunity is a relevant host factor shaping microbial ecology in the gut, and that its impact was most pronounced on SI-resident bacterial communities. Conclusion Our data also clearly establishes that MhcII-mediated cognate interactions between B cells and T cells regulates this effect by maintaining species richness in the gut, which is a phenotype commonly associated with good health. Finally, contrary to expectations, our experimental results indicate that IgA was not responsible for driving any of the effects on the microbiota ascribed to the loss of B cell-specific MhcII. Collectively, results from our experiments support that MhcII-mediated antigen presentation by B cells regulates microbiota composition and promotes species richness through an IgA-independent mechanism.